The impact of the experience and gender of the professor of physical education and sports to raise the motivation of the performance of motor skills in the secondary stage students of some high school in the state of Djelfa A field study in some of the mu - amar gedid; جزار نسيمة; douar riad (sports creativity, 2025)
The objective of our current study is to highlight the role played by some of the personal variables (professional experience, academic composition, gender) of the professor of education and physical to raise the motivation of the performance of the motor skills of secondary stage students The study population consisted of 5801 students in the secondary stage. The sample of the study was 192 secondary school students We found that tribal gains, seniority, and pedagogic formation influence the increase in the skillful performance of students in the secondary stage. This is why we have examined the subject of our research, ( professional experience , academic composition ,gend) professor of physical education and sports to increase the motivation of motor performance skills of the students of the secondary stage for some high schools Djelfa. " Keywords: experience, professor of physical and athletic education, motivation of motor skills ,sport similitescourses in planning for sustainable development as well as encouraging ideas Innovations as well as scientific studies in the field of sustainable development and its applications in the field of sports and benefit from international experiences by signing cooperation agreements with the leading countries in this field, In addition to expanding the concepts of sustainable development to include other economic sectors.